2018
DOI: 10.1089/ten.tec.2018.0219
|View full text |Cite
|
Sign up to set email alerts
|

Human Synovial Mesenchymal Stem Cells Good Manufacturing Practices for Articular Cartilage Regeneration

Abstract: Background: Cartilage restoration is a desperately needed bridge for patients with symptomatic cartilage lesions. Chondral lesion is a pathology with high prevalence, reaching as much as 63% of general population and 36% among athletes. Despite autologous chondrocyte implantation versatility, it still fails to fully reproduce hyaline articular cartilage characteristics. Mesenchymal stem cells (MSCs) may be isolated from various known tissues, including discarded fragments at arthroscopy such as synovial membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 37 publications
(54 reference statements)
3
35
0
Order By: Relevance
“…A comparable yield of cells from synovium have been isolated from pathological knee and hip joints exhibiting a “mixed” cell‐surface marker profile similar to this study . Furthermore, a similar cell‐surface marker expression profile for synovium‐derived trilineage positive cells has been reported in this study, though the authors have interpreted CD166 as a possible discriminating factor between multipotent and fibroblastic cells . In contrast, assessing the ameliorative effects of synovial MSCs in an osteoarthritic mouse model, synovial MSCs were reported to be highly positive for CD73, CD90, and CD105 .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…A comparable yield of cells from synovium have been isolated from pathological knee and hip joints exhibiting a “mixed” cell‐surface marker profile similar to this study . Furthermore, a similar cell‐surface marker expression profile for synovium‐derived trilineage positive cells has been reported in this study, though the authors have interpreted CD166 as a possible discriminating factor between multipotent and fibroblastic cells . In contrast, assessing the ameliorative effects of synovial MSCs in an osteoarthritic mouse model, synovial MSCs were reported to be highly positive for CD73, CD90, and CD105 .…”
Section: Discussionsupporting
confidence: 81%
“…While the hematopoietic marker CD34 was absent, there was variable expression of CD45 and MHC‐II, indicating potential inclusion of leukocytic cells from perivascular tissue. However, these profiles are not dissimilar to recent studies of synovial MSCs derived from inflammed human knee joints . Hagmann et al reported differences between donor‐typed bone marrow and synovial MSCs with the latter uniformly exhibiting trilineage differentiation and strongly positive for CD73, CD90, CD105, and MHC‐I although small levels of CD34 and CD45 positive cells were also detected.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…ACI is a two-step procedure that consists of healthy cartilage harvesting through arthroscopy followed by the expanded cell culture and, in a second step, cartilage defect filling (13)(14)(15). In spite of second and third ACI generations' versatility, those techniques use healthy cartilage tissue, "in vitro" related chondrocytes dedifferentiation and still fails to fully reproduce the hyaline characteristics of the original articular cartilage (6,13,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%